Competency model of Indonesian construction laborers in Malaysia - Ismail, Fadillah; Saimy, Intan Sazrina; Md. Yusoff, Rosman; Yusoff, Anis Yusal; Chan, Shiau Wei; Umi, Kartini Rashid (Science Publishing Corporation, 2018)
Quality of human resources is a significant factor to improve high productivity performance of an organization or industry. The quality of human resources can be indicated through competence, skills, ability and other specific characteristics of employee to build a teamwork within organization. Competency-Based on training emphasizes what an employee can do more than how much they know. Hence, through a mixed research method using explanatory approach, this study aims to build a model of Indonesian labor competency based on the competence of 300 Indonesian construction laborers in Malaysia. This model emphasizes four criteria of competency which are communication, skills, interpersonal, and attitude. The finding showed that Indonesian labor force is competent in communication, interpersonal, and attitude. However, Indonesian labor force is seen to be incompetent in criterion skills and still needs training to improve their skills to be in line with the industry needs